2005
DOI: 10.1002/art.21345
|View full text |Cite
|
Sign up to set email alerts
|

Use of the plasma stromelysin (matrix metalloproteinase 3) concentration to predict joint space narrowing in knee osteoarthritis

Abstract: Conclusion. The baseline MMP-3 level was a significant predictor of JSN in this pilot study. Moreover, serial plasma MMP-3 levels reflected concurrent JSN in the placebo group over the 30-month period of observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 29 publications
5
46
0
Order By: Relevance
“…Therefore, it is likely that this mechanism of action contributes to the in vivo anti-inflammatory and anticatabolic effects of CS-GlcN. The baseline MMP-3 level in serum is a significant predictor of joint space narrowing in knee OA [63]. In addition, serum MMP-3 levels in knee OA patients are significantly greater in generalized OA compared with non generalized disease [64].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is likely that this mechanism of action contributes to the in vivo anti-inflammatory and anticatabolic effects of CS-GlcN. The baseline MMP-3 level in serum is a significant predictor of joint space narrowing in knee OA [63]. In addition, serum MMP-3 levels in knee OA patients are significantly greater in generalized OA compared with non generalized disease [64].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MMP-3 levels correlate with erosive disease in RA patients despite the finding of normal CRP levels (52), and associations between MMP-3 gene promoter polymorphisms and radiographic outcome in RA have been described (53)(54)(55). Studies of conditions that are traditionally considered noninflammatory, such as osteoarthritis, have also suggested that MMP-3 levels can predict radiographic joint space narrowing (56). The ability of MMP-3 to act as a proteinase with a broad substrate profile and its ability to activate collagenase support the notion that it plays a complex role in pathologic processes.…”
Section: Young-min Et Almentioning
confidence: 94%
“…Also interestingly, MMP-3 was found to be increased in plasma shortly after injury, perhaps as a reflection of synovial activation and inflammation [20,21]. Interestingly, plasma levels of MMP-3 were shown to be predictive of knee joint space narrowing over 16 months in a prospective, longitudinal OA clinical trial [22].…”
Section: Introductionmentioning
confidence: 95%